EMDR as Add-On Treatment for Psychiatric and Traumatic Symptoms in Patients with Substance Use Disorder - Carletto, Sara; Oliva, Francesco; Barnato, Micaela; Antonelli, Teresa; Cardia, Antonina; Mazzaferro, Paolo; Raho, Carolina; Ostacoli, Luca; Fernandez, Isabel; Pagani, Marco (Frontiers in Psychology, 2018)
Background. Substance use disorders (SUD) are patterns of substance use leading to severe impairment on social, working and economic levels. In vivo and clinical findings have enhanced the role of the brain’s stress-related system in maintaining SUD behaviors. Several studies have also revealed a high prevalence of post-traumatic symptoms among SUD patients, suggesting that a trauma-informed treatment approach could lead to better treatment outcomes. However, only few studies have evaluated the use of eye movement desensitization and reprocessing (EMDR) in SUD without consistent results. The aim of the present pilot study was to assess the efficacy of a combined trauma-focused (TF) and addiction-focused (AF) EMDR intervention in treating post-traumatic and stress-related symptoms of patients with SUD. Methods. Forty patients with different SUD were enrolled in the study. Twenty patients underwent treatment as usual (TAU), the other 20 patients were treated with TAU plus 24 weekly sessions of EMDR. All patients were assessed before and after intervention for several psychological dimensions using specific tools (i.e. BDI-II, DES, IES-R, STAI, and SCL-90-GSI). A repeated measure MANOVA was performed to evaluate both between groups (TAU+EMDR vs. TAU) and within group (pre vs. post-intervention) effects and interactions. A secondary outcome was the dichotomous variable yielded by the urine drug testing immunoassay (yes/no). Results. The RM-MANOVA revealed both a significant pre–post main effect (p < .001), and a significant group-by-time main effect (p< .001). Significant improvements on IES-R, DES and SCL-90-GSI scales were shown in both groups according to time effects (p<0.05). However, significant greater effects were found for TAU+EMDR group than TAU group. No differences were found between TAU and TAU + EMDR groups in terms of urine drug immunoassay results before and after the interventions. Conclusions. The TAU+EMDR group showed a significant improvement of post-traumatic and dissociative symptoms, accompanied by a reduction in anxiety and overall psychopathology levels, whereas TAU group showed a significant reduction only in post-traumatic symptoms. Although our results can only be considered preliminary, this study suggests that a combined TF- and AF- EMDR protocol is an effective and well-accepted add-on treatment for patients with SUD.